Determinants of Parental Attitudes towards Children’s Vaccination in Lithuania: An Online Survey - Čeponytė, Kamilė; Narkevičiūtė, Eglė; Beržanskytė, Aušra; Burokienė, Sigita (Acta medica Lituanica, 2024)
Background: Data from recent years show that the COVID-19 pandemic has significantly reduced the scope of child immunisation worldwide. If the numbers continue to fall, we may have a vaccination crisis. In order to understand the local factors of this phenomenon, we studied parents‘ viewpoint towards childhood vaccination in Lithuania. Therefore, the aim of our study was to determine the impact of parental attitudes on children’s vaccination.Materials and Methods: A web-based cross-sectional study was made in Lithuania from October 20th to November 3rd, 2020, using Google Forms. An anonymous questionnaire included both quantitative and qualitative questions. The questionnaire was distributed to the general population in Lithuania via social media and a snowball sampling. Only parents who have at least one child under 18 years old were involved in the study. We analysed the parents’ attitudes towards vaccination by their socioeconomic and demographic determinants using MS Excel and OpenEpi tools. The respondents were considered vaccine supporters if they vaccinated all their children with state-reimbursed vaccines or only vaccinated some of their children, and vaccine sceptics if they did not vaccinate their children with state-reimbursed vaccines.Results: The population of our research consisted of 775 parents. There were more males against vaccination than females, respectively, 59.6% and 33.2%. 65.0% of all respondents stated that they vaccinated their children with the full course of vaccines, while the remaining 35.0% did not vaccinate. University-level education dominated in both pro-vaccine and anti-vaccine groups. We found that 16.9% of parents who were unvaccinated as children themselves tend not to vaccinate their children. However, in the pro-vaxx group, only 0.7% of parents were unvaccinated during childhood. 50.8% of vaccine sceptics were not fully informed by healthcare professionals about the benefits and risks of vaccination, while only 31.6% of vaccine supporters were not informed. Social environment did not have an impact on the decision whether to vaccinate or not to vaccinate a child among both vaccine advocates and vaccine deniers (accordingly, 51.2% and 42.9%). 29.3% of respondents stated that the cost of paid vaccinations was too high. Open-text survey responses gave us more in-depth insight about the parental decision-making process. Protection of children and society from infectious diseases (31.7%) was mentioned as the main reason for vaccination. Whereas vaccine-hesitant parents were mostly concerned about already-occurring side effects or their risk (43.4%).Conclusions: Our findings confirmed that vaccine hesitancy was associated with not being vaccinated in childhood themselves, lack of information from medical practitioners and male gender. The price of vaccines also had an impact on immunisation rates – more than one-third of the vaccine supporting parents indicated that the cost of paid vaccinations was too high. The main incentive for vaccine compliance was parents’ desire to protect their children and society from infectious diseases. Whereas vaccine-hesitant parents were mostly concerned about already occurring side effects or their risk. There was no consensus, whether vaccination of children should be mandatory in Lithuania, as the answers to the question were almost evenly distributed. The formation of parents‘ attitudes towards children‘s vaccination is a complex process that is determined by parents‘ attitudes towards the health care system, lack of trust in doctors, and gaps in communication about the benefits and risks of vaccination. All of this information should be taken into account in health policy-making.